Impact of the cost overrun factors on the project delays in construction industry - Noor Elinah, Sailin (2018)
Delays and cost overruns are evidently frequent problems in the construction industries of many developed and developing countries. Cost saving and time performances are usually essential to all parties who are involved in a construction project that is owner, contractor, and subcontractor. The main causes of disputes in construction projects involve delay and failure to complete the work in the specified cost and time frame. The purpose of this study is to assess factors leading to time overruns (delays) and cost overruns in construction projects in the Malaysia. A total of 36 factors were identified from previous studies. The data collections were carried out using structured questionnaire survey. 50 respondents from the construction industry in Malaysia participated in the survey questionnaire. There are two variable in this study which are independent variables (Cost overrun factors) and dependent variable (Project delay).The results indicate that the all the cost overrun factors has a positive relationships with the project delay. Finding in this study is beneficial to employer to understand how important cost overruns factors to project delay, as well as to prevent recurrences from happening in construction industry.